1993
DOI: 10.1111/j.1365-313x.1993.tb00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of elicitor‐induced lipoxygenase in tobacco cells

Abstract: SummaryLipoxygenase activity was induced in a tobacco cell suspension culture by treatment with glycopeptide elicitors prepared from the cell walls of Phytophthora parasitica var, nicotianae, and in tobacco seedlings infected by this fungal pathogen. Upon purification and characterization, the enzyme appeared to have a molecular weight of 96000, a pl of 5.1 and a Km of 20.9 μM with linoleic acid as substrate. According to its acidic optimum pH, it belongs to type‐2 lipoxygenases. Using linoleic, linolenic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1
2

Year Published

1993
1993
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 37 publications
2
40
1
2
Order By: Relevance
“…nPG strongly inhibits the activity of a tobacco lipoxygenase that may be involved in JA biosynthesis from LA (Fournier et al, 1993) and has been shown to inhibit wound-induced expression of pin and vsp genes (Staswick et al, 1991;PeÍía-Cortes et al, 1993). In parsley cells nPG was partially effective in reducing the elicitorinducible expression of 4CL, PAL, and TyrDC but was ineffective in reducing EL13 or HRGP expression.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…nPG strongly inhibits the activity of a tobacco lipoxygenase that may be involved in JA biosynthesis from LA (Fournier et al, 1993) and has been shown to inhibit wound-induced expression of pin and vsp genes (Staswick et al, 1991;PeÍía-Cortes et al, 1993). In parsley cells nPG was partially effective in reducing the elicitorinducible expression of 4CL, PAL, and TyrDC but was ineffective in reducing EL13 or HRGP expression.…”
Section: Discussionmentioning
confidence: 94%
“…The ability of nPG to effectively inhibit plant oxygenases and thus biosynthesis of jasmonates via the octadecanoid pathway is related to its activity as an antioxidant, free radical scavenger (Staswick et al, 1991;Fournier et al, 1993). Activated oxygen species are produced following elicitor treatment of parsley cells (Niirnberger et al, 1994), and such species could play a role in elicitor-induced signal transduction (Aposto1 et al, 1989;Devlin and Gustine, 1992;Mehdy, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In tobacco, 9-hydroperoxides are expected to be formed by NtLOX1, an elicitor-and pathogen-inducible 9-LOX (Fournier et al, 1993;Véronési et al, 1996). Therefore, the ability of NtDES1 to utilize hydroperoxides formed through NtLOX1 action was investigated in a qualitative thin-layer chromatography (TLC) assay.…”
Section: Ntdes1 and Ntlox1 Can Cooperate In Vitro To Form 9-dvesmentioning
confidence: 99%
“…Thus, 9-LOX gene expression and 9-LOX activity are strongly induced in tobacco and potato in response to two oomycete pathogens of these plants, Phytophthora parasitica var. nicotianae (Ppn) and Phytophthora infestans, respectively, and to oomycete-derived elicitors (Fournier et al, 1993;Véronési et al, 1996;Fidantsef and Bostock, 1998;Kolomiets et al, 2000;Gö bel et al, 2001). Similarly, expression of the 9-DES gene StDES is increased in potato in response to elicitors and pathogen attack (Stumpe et al, 2001).…”
mentioning
confidence: 99%